単独の予測可能な有限モデルにおいて複数の人間工学的リスク要因を組み合わせること (2024)
軟組織をモデル化する方法は、第１の対象の解剖学的幾何学形状を示す１又は複数の画像を受信することを含む。解剖学的幾何学形状には軟組織が含まれる。本方法はまた、第１の対象に取り付けられた１又は複数のセンサを使用して、第１の対象の解剖学的幾何学形状の複数のパラメータを測定することを含む。本方法はまた、第１の対象、第２の対象、又はその両方の軟組織について第１の材料特性のセットを受信することを含む。本方法はまた、第１の対象がタスクを行っている間に、軟組織を特徴付ける第２の材料特性のセットを特定することを含む。本方法はまた、１若しくは複数の画像、パラメータ、第１の材料特性のセット、及び第２の材料特性のセットに少なくとも部分的に基づき、軟組織に対する歪み、軟組織に対する応力、又はその両方を決定することを含む。【選択図】図６ A method for modeling soft tissue includes receiving one or more images showing an anatomical geometry of a first subject. The anatomical geometry includes a soft tissue. The method also includes measuring a plurality of parameters of the anatomical geometry of the first subject using one or more sensors attached to the first subject. The method also includes receiving a first set of material properties for the soft tissue of the first subject, a second subject, or both. The method also includes identifying a second set of material properties that characterizes the soft tissue while the first subject performs a task. The method also includes determining a strain on the soft tissue, a stress on the soft tissue, or both based at least partially upon the one or more images, the parameters, the first set of material properties, and the second set of material properties.